The Effect of Kaisa Method on The Increase of Short Surah Memorization for 4-6 Year-Old-Children - Ma'rufah, Durrotun; Windiarti, Rina (BELIA: Early Childhood Education Papers, 2020)
This study aims to determine the effect of the Kaisa Method on the increase of short surah memorization for 4-6 year-old children. This research was conducted at Aisyiyyah Bustanul Athfal 61 Kindergarten, Sampangan Semarang by using the method of pre-experiment design through One Group Pretest-Posttest. The sample used in this study amounted to 32 children in the age of 4-6 years. The sampling technique in this study was purposive sample. The results of the pretest and posttest have an average value (mean) of short surah memorization, on the pretest is 68.44 while on the posttest is 96.44 so that the increase is 28. The significance of the results of the hypothesis test using the T-Test shows the significance value is more smaller than 0.05. That is 0,000 <0.05. Thus, it can be concluded that there is a significant effect of the Kaisa Method on the increase of short surah memorization for 4-6 year-old-children at Aisyiyah Bustanul Athfal 61 Kindergarten Sampangan, Gajah Mungkur District, Semarang City.